Development of electronic modules of Mucuna pruriens L. to improve students' critical thinking skills - Ikmi Marlina; Endang Widi Winarni; Euis Nursa'adah (University of Muhammadiyah Malang, 2026)
Background: The development of a research-based electronic module on Mucuna pruriens L. is important because contextual and innovative learning resources are needed to connect scientific findings with excretory system concepts while improving students’ critical thinking skills. Objectives: This study aimed to develop a research-based e-module derived from findings on the effect of Mucuna pruriens L. leaf extract on burn wound healing in mice (Mus musculus), and to determine its validity and effectiveness in improving students’ critical thinking skills. Methods: This study employed the 4D research and development model consisting of Define, Design, Develop, and Disseminate stages. The product was validated by five experts, and its effectiveness was tested through pretest and posttest scores. Results: The experimental study showed that Mucuna pruriens leaf extract accelerated burn wound healing, with the P3 group at the highest concentration demonstrating the best healing outcome on day 14. Based on these findings, a contextual e-module on the excretory system was developed. Expert validation yielded an Aiken’s V value of 0.94, indicating that the e-module was highly valid and feasible for use. The effectiveness test showed improvement in students’ critical thinking skills, with an N-gain score of 0.45 in the experimental class (medium category) and 0.29 in the control class (low category). Conclusion: The developed e-module met the validity and feasibility criteria and was effective in supporting research-based learning on the excretory system and enhancing students’ critical thinking skills.